Fondasi Qur’ani Tata Kelola Pendidikan Islam: Studi Tentang Amanah dan Keadilan - Junaina Junaina; Merita Diana; Muhammad Akmansyah (Lentera: Jurnal Ilmiah Kependidikan, 2026)
Governance of Islamic educational institutions currently faces serious challenges regarding professionalism, accountability, and transparency, which often clash with practices of nepotism and inefficient management. This study aims to construct a foundation for Islamic education governance based on Quranic values by examining QS. an-Nisā’ (4):58. Using a qualitative library research method with a thematic exegesis (tafsir maudhu’i) approach combined with educational management analysis, this study explores classical and contemporary interpretations of the concepts of amanah (trust) and justice. The findings indicate that the transformation of the concept of amanah within the context of educational management yields principles of meritocracy in human resource recruitment (professionalism), transparency in fund and asset management (accountability), and curriculum integrity (intellectual trust). Meanwhile, the concept of justice (al-‘adl) transforms into objectivity in decision-making, distributive justice in the compensation system (equity), and equitable access to education (inclusivity). The synthesis of these two values forms a model of Good Islamic Governance or Prophetic Educational Governance, where theological spirit is integrated into practical managerial instruments as the main pillars of quality assurance in Islamic educational institutions.